To Teach Higher Education Students General Didactic Principles and Methods of using New Pedagogical Technologies in Music Culture Lessons - Mavludaxon Rahimova Nabijonovna (International Journal on Orange Technologies, 2021)
The famous historian Sharafiddin Ali Yazdi in his book "Zafarnoma" spoke about the musical conferences held during the reign of Amir Temur. And the Turks, the Mongols, the Chinese, the Arabs, and the Ajamids all sang with their pictures. ” The use of various pedagogical technologies in music education classes aimed at shaping the creative thinking of students is a factor in achieving guaranteed results in music education. This article describes the methods of teaching higher education students the general didactic principles and methods of using new pedagogical technologies in the lessons of music culture.